2012
DOI: 10.3922/j.psns.2012.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual and auditory stimuli in a choice reaction time task.

Abstract: The effect produced by a warning stimulus(i) (WS) in reaction time (RT) tasks is commonly attributed to a facilitation of sensorimotor mechanisms by alertness. Recently, evidence was presented that this effect is also related to a proactive inhibition of motor control mechanisms. This inhibition would hinder responding to the WS instead of the target stimulus (TS). Some studies have shown that auditory WS produce a stronger facilitatory effect than visual WS. The present study investigated whether the former W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thompson et al (1992), Shenvi and Balasubramanian (1994), Pain and Hibbs (2007), Shelton and Kumar (2010), and Ng and Chan (2012) have documented that the auditory RT is faster than the visual RT; in contrast, Verleger (1997) and Yagi et al (1999) showed that the visual RT is faster than the auditory. McAuley and Henry (2010) examined modality effects in rhythm processing using a tempo judgment paradigm, finding that auditory rhythms demonstrate an advantage over visual rhythms; analogously, Bueno and Ribeiro do Valle (2012) studied the effect produced by the warning stimulus modality in a reaction time task, and they found that an auditory warning stimulus exerts a stronger inhibitory influence on responsivity than a visual warning stimulus. In contrast, visual temporal reference memory may be more permanent than auditory reference memory, although auditory temporal information and visual temporal information do not mutually interfere in reference memory (Ogden et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Thompson et al (1992), Shenvi and Balasubramanian (1994), Pain and Hibbs (2007), Shelton and Kumar (2010), and Ng and Chan (2012) have documented that the auditory RT is faster than the visual RT; in contrast, Verleger (1997) and Yagi et al (1999) showed that the visual RT is faster than the auditory. McAuley and Henry (2010) examined modality effects in rhythm processing using a tempo judgment paradigm, finding that auditory rhythms demonstrate an advantage over visual rhythms; analogously, Bueno and Ribeiro do Valle (2012) studied the effect produced by the warning stimulus modality in a reaction time task, and they found that an auditory warning stimulus exerts a stronger inhibitory influence on responsivity than a visual warning stimulus. In contrast, visual temporal reference memory may be more permanent than auditory reference memory, although auditory temporal information and visual temporal information do not mutually interfere in reference memory (Ogden et al 2008).…”
Section: Introductionmentioning
confidence: 98%